Hollow carbon cavities decorated with highly dispersed manganese-nitrogen moieties for efficient metal-air batteries. (1st April 2022) - Li, Qingyu; Zhao, Tong; He, Caimei; Cai, Yezheng; Wu, Qiang; Huang, Youguo; Liu, Kui; Ma, Zhaoling; Wang, Hongqiang
Highlights: Hollow carbon cavities decorated with highly dispersed Mn-N moieties were developed. The hollow carbon cavities endowed the developed Mn-NC with considerable ORR catalytic activity in both alkaline and neutral electrolyte. The Mn-NC-driven ZAB and MAB exhibited impressive discharge performance than those driven by commercial Pt/C catalyst. Abstract: The designed synthesis of hollow carbon chamber catalysts is central for accelerating the oxygen reduction reaction (ORR) electrocatalysis, which is the core process of renewable metal-air batteries. Nevertheless the positive effect of hollow carbon cavities on the actual ORR electrocatalysis in alkaline and neutral medium is still underexplored. Herein, manganese-decorated zeolite imidazolate frameworks coated with polydopamine (PDA) was pyrolyzed to form the hollow and macroporous carbon cavities decorated with highly dispersed manganese-nitrogen moieties (Mn-NC). The hollow carbon cavities with spacious microchemical environment can maximize the amount of atomically active sites and provide convenient mass transfer channels, cooperatively boosting the alkaline and neutral ORR via an efficient close to four-electron pathway. As result, the hollow Mn-NC exhibited much enhanced catalytic capability than Mn-C synthesized without polydopamine coating in both alkaline and neutral electrolyte. When utilized as a cathode catalyst, the homemade zinc-air battery (ZAB) and magnesium-air battery (MAB) driven by Mn-NC displayed higher peak power density and longer stable discharge time than those driven by commercial Pt/C catalyst, along with robust rate performance, showing appreciable application potential. This work may inspire more study on rational design and synthesis of hollow catalysts with boosted ORR electrocatalysis for efficient energy conversion devices including fuel cells and other metal-air batteries and beyond. Graphical abstract: Image, graphical abstract